ANALISIS TINGKAT KELAYAKAN APLIKASI ANDROID “CHEMICAL LAB WORK GUIDE” SEBAGAI MEDIA PEMBELAJARAN - Puji Setiyowati; Endang Triwahyuni Maharani; Andari Puji Astuti (Universitas Muhammadiyah Semarang, 2018)
This research aims to know the feasibility of the android application “Chemical Lab Work Guide” as theoritical learning media. The theoritical feasibility of the media is viewed from the aspect of material feasibility and media feasibility. The feasibility of the material includes the truth of the concept, the mathematics and the clarity of the practical steps, implementation, evaluation and assignment, and learning strategies. While the feasibility of the media includes language, visual display, software engineering, information about the media, and response /feedback. The development research used ADDIE model. The subject of the research were material experts and media experts. Data collection techniques were carried out using questionnaires with the type of choice. Data analysis uses quantitative data analysis. The research results obtained are android application received an assessment from material experts getting a score of 99.3 with a conversion of 4.5, so that it falls into the very feasible category. Then the assessment of the media experts got a score of 90 with a conversion of 4.1, so that it was in the decent category. The high value of material and media feasibility, showsthat the Android application